Pembagian Harta Bersama Paska Perceraian Melalui Proses Mediasi Di Pengadilan Agama Kelas 1A Pontianak - Harumalina, Okta Dasa; Hazilina, Hazilina; Lestari, Nina Niken (Res Judicata, 2024)
The division of joint assets after divorce is an issue that often causes disputes between former spouses, considering the importance of justice and balance in the distribution of assets acquired during the marriage. This study aims to assess the effectiveness of the mediation process in the Pontianak Class 1A Religious Court as an alternative solution for resolving disputes over the division of joint assets post-divorce. Mediation is chosen for its ability to reduce prolonged conflicts, save costs, and expedite dispute resolution compared to formal judicial processes. The research method used is a qualitative approach with data collection techniques through in-depth interviews and document analysis. The results of the study indicate that the mediation strategies applied include comprehensive case analysis covering legal, factual, and psychological aspects; building trust and empathy through effective communication; a collaborative approach that prioritizes cooperation between parties; providing accurate legal information to ensure fairness; managing emotions and conflicts to prevent escalation; and drafting agreements that are sustainable and can be well implemented. Evaluation of the mediation process is also conducted to identify areas for improvement and ensure increased effectiveness in the future. Thus, mediation at the Pontianak Class 1A Religious Court has proven to be an effective mechanism in resolving disputes over the division of joint assets post-divorce, providing fair, sustainable, and satisfactory solutions for the parties involved. Keywords: Division of Joint Assets, Divorce, Mediation.